Answer:
1/216
Step-by-step explanation:
So your gonna Multiply each term in the first parentheses by each term in the second parentheses “ -5x5-5i-5x2i-2ix i ” than multiply the numbers “ -25 -5i -5x2i -2ixi ” that’s your answer!
Hello XD
3(x+2) = 3x+6
Distributive property
(3)(x)+(3)(2) = 3x+6
3x+ 6 = 3x+6
Now subtract 3x from both sides
3x+6-3x = 3x+6-3x
6=6
Subtract 6 from both sides
6-6 = 6-6
0=0
In this case the answer is : All real numbers are solution
Answer:
2y+1+9x is written as a product of three factors